PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK JELAJAH KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Marwati, Sofa; Rosidin, Odien; Yuliana, Rina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the development process, feasibility, and student responses to the "Big Book Jelajah Kata" learning media. The research used a Research and Development (R&D) method with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The outcome of this research and development is the "Big Book Jelajah Kata" learning media, which can be used for early reading instruction. The study was conducted at SD Negeri Cilaku with the research subjects being 31 first-grade students. The data collection techniques and procedures included interviews, observations, documentation, tests, questionnaires, and expert validation tests. The media expert validation received an average score of 87.6%, the material expert validation received an average score of 84.9%, and the language expert validation received an average score of 89%. Based on the expert validation results, the accumulated score was 87.16%, which falls into the "very feasible" category. The student response questionnaire received an average score of 97.8%, and the early reading skills test received a score of 91.86%. Therefore, it can be concluded that the "Big Book Jelajah Kata" learning media is highly feasible and very effective for use in early reading instruction in first-grade elementary school classes.